Financial Performance Differences Based on Capital Structure in Indonesian Fmcg Companies (2019-2023) - Khikmah, Putri Ainul; Tojibussabirin, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study examines differences in financial performance based on different capital structure levels in Fast Moving Consumer Goods (FMCG) companies operating in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023. A quantitative approach was used using financial ratios obtained from secondary data of five selected companies. The Kruskal-Wallis test was applied as a non-parametric alternative to ANOVA because the data did not meet the assumptions of normality and homogeneity. The results showed significant differences in Return on Assets (ROA) and Return on Equity (ROE) among the Debt to Equity Ratio (DER) categories. In contrast, no significant difference was observed in Net Profit Margin (NPM). These findings emphasize the importance of capital structure decisions in enhancing certain aspects of financial performance in the FMCG industry.